Ecotourism, Environmental Impacts and Sustainability in the Himalayan Settlements: Study of Sagarmatha (Mt. Everest) National Park, Nepal - Bhatta, Kishan Datta; Roger C.K Chan (Himalayan Journal of Applied Science and Engineering, 2023)
Nepal has advocated for ecotourism as a strategy to support community development vis-a-vis environmental protection in the Protected Area settlements. In this context, considering the case of settlements along the Everest trail in the Sagarmatha (Mt. Everest) National Park, this paper aims to critically examine the environmental impacts of ecotourism, local community’s perceptions towards ecotourism development and its contribution towards achieving sustainability in the region. It has adopted case study as a research strategy and used qualitative approach for detailed investigation. It adopted multiple sources of data collection such as key informants interview, household’s survey, participant observation and archival research. This study concludes that current approach of tourism development and planning does not satisfy the objectives of ecotourism development. It has neither equitably benefitted local residents nor significantly reduced the use of forest resources, environmental degradation, and deterioration of cultural and built heritage. It will further continue inducing impacts on local environment, culture, and communities heading tourism and the destination towards unsustainability. A sustainable approach to ecotourism is needed that integrates local knowledge, skills and cultural values that support conservation agendas, and encourage inclusive participation of communities, stakeholders and promote sustainability.